PERANCANGAN SISTEM OTOMASI PENGUNCI PINTU MENGGUNAKAN E-KTP BERBASIS IOT SMARTPHONE - Ichsan Maulana; Sujono Sujono; Peby Wahyu Purnawan (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
This paper discusses a door lock automation system using IoT-based e-KTP that will be monitored using a smartphone. The system consists of HC-SR04 ultrasonic sensor, Radio Frequency Identification (RFID), and EasyVR 3. HC-SR04 ultrasonic is used to detect the presence of door access users. The RFID sensor is a medium for entering the access code in the form of Unique Identification (UID), and the EasyVR 3 sensor is used to detect passwords in the form of voice signals from access users. To record the real-time of door access users, Real Time Clock DS3231 is used. The microcontroller used to manage the system's work is Arduino Mega 2560. NodeMCU ESP 8266 sends data to a smartphone as a monitoring device. MG90S servo is used to drive the door opening/closing mechanical system. To get access, users must register by entering e-KTP UID data and passwords as sound signals. Testing is carried out to evaluate the performance of the system that has been made. The test scenarios consist of door access from the inside and door access from the outside, each for users who have access and those who do not have access. The test results show that the system can secure door access only for users with access. Monitoring the system using a smartphone can work well where every instance of access use can be monitored user data and access time. However, there are still weaknesses in the mechanical part of opening / closing the door where the servo fails to open and close.